PELOD-2 Score Mortality Prediction Ability in Children with Multiple Organ Dysfunction - Anh Tuan, Ta; Thi Lan, Dinh (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 37 No 3, 2021)
This study evaluates PELOD-2 score mortality prediction ability in children with multiple organ dysfunction. The descriptive cross-sectional study was carried out on 110 children with Multiple Organ Dysfunction at the Pediatric intensive care unit in Vietnam National Children’s Hospital from 1 st January 2015 to 31 th June 2016. The study results show that the average PELOD-2 score was high (8.8 ± 3.85 points); the PELOD-2 score of the mortality group was significantly higher than the survivor group with 7.07 ± 2.37 and 10.43 ± 4,28, respectively; mortality rate was directly proportional to PELOD-2 score; the PELOD-2 score could separate the mortality group from the survivor group with the area under the ROC curve of 0.76 and the cut-point PELOD-2 score   of 8.5. If children with multiple organ dysfunction had over 10 points of PELOD-2 score, their mortality prediction  value was nearly the same as the actual mortality rate. The study concludes that PELOD-2 score was significantly correlated with associated multiple organ dysfunction syndrome and useful in predicting mortality. Keywords: Multiple organ dysfunction, PELOD-2 score. References [1] B. Goldstein, B. Giroir, A. Randolph, International Pediatric Sepsis Consensus Conference: Definitions for Sepsis and Organ Dysfunction in Pediatrics. Pediatric Critical Care Medicine, Vol. 6, 2005, pp. 2-8. [2] J. D. Wilkinson et al., Mortality Associated with Multiple Organ System Failure and Sepsis in Pediatric Intensive Care Unit, The Journal of Pediatrics, Vol. 111, 1987, pp. 324-328 [3] J. A. Tantaleán et al., Multiple Organ Dysfunction Syndrome in Children, Pediatric Critical Care Medicine, Vol. 4, 2003, pp. 181-185 [4] T. K. Hao, Clinical Characteristics and Prognostic Value of PELOD Score in Pediatric Population With Multi-Organ Dysfunction, 11th Pediatric National Conference, 2014 (in Vietnamese). [5] S. Leteurtre et al., PELOD-2: An Update of the Pediatric Logistic Organ Dysfunction Score, Critical Care Medicine, Vol. 41, 2013, pp. 1761-1773. [6] J. P. Gonçalves et al., Performance of PRISM III and PELOD-2 Scores in A Pediatric Intensive Care Unit, European Journal of Pediatrics, Vol. 174, 2016, pp. 1305-1310. [7] T. K. Hao, Evaluation of PMODS Score in Patients with Multi-organ Dysfunction Syndrome at A Pediatric Intensive Care Unit, Journal of Practical Medicine, Vol. 805, 2012 (in Vietnamese).